2006
DOI: 10.1111/j.1468-5884.2006.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

The context of intergroup belief cross wherein minority members maintain consistency: Belief minority and majority in a categorical in‐group and out‐group1

Abstract: The present study investigated the social conditions required for minority members to preserve their attitudinal and behavioral consistency in an intergroup context. In the experiment, intergroup belief crosses wherein a belief minority (or majority) in a categorical in-group was reversed as a majority (or minority) in an out-group were manipulated. It was hypothesized that individuals supported by the majority in the categorical in-group would preserve their attitudes and behavioral intentions even though the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…In this situation, it would be difficult to express opinions that differed from the in‐group majority, perhaps preventing the need for differentiation from being evoked. In contrast to the present study, Nonami (2006) reported that in addition to the effect of being positioned as the majority of the in‐group, congruency with the majority of the out‐group was also effective in preserving attitudinal and behavioral consistency in an ideological task (evaluation of a bio‐ethical problem) in which individuals decided their opinions privately. Further research is needed to elucidate the difference between group and personal decision‐making tasks on the consistency of minority members.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this situation, it would be difficult to express opinions that differed from the in‐group majority, perhaps preventing the need for differentiation from being evoked. In contrast to the present study, Nonami (2006) reported that in addition to the effect of being positioned as the majority of the in‐group, congruency with the majority of the out‐group was also effective in preserving attitudinal and behavioral consistency in an ideological task (evaluation of a bio‐ethical problem) in which individuals decided their opinions privately. Further research is needed to elucidate the difference between group and personal decision‐making tasks on the consistency of minority members.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present experiment, participants were concerned with group strategic decisions based on their role in a company: this is defined as a group task. In addition, in order to exclude the effects of the superordinate category found in Nonami (2006), the boundary between the in‐group and out‐group was emphasized by the description of a context consisting of two different companies. This disrupted their mobility from the in‐group to the out‐group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations